Analyse morphosyntaxique des productions écrites des élèves de la 5ème année secondaire de quelques écoles de la ville de Kisangani dans la province de la Tshopo en République Démocratique du Congo - Lukombe, Jacques MUKONKOLE (IJRDO- Journal of Educational Research, 2021)
This article focuses on the morphosyntactic dysfunctions of the written productions of the students of the 5th year of secondary of some schools in the city of Kisangani. The aim was to analyse the pupils' copies and to identify the various grammatical breaches committed. The wrongful sentences were opposed to those deemed correct before determining the causes of these various faults. The objective of this article is to contribute to the improvement of the practice of French by students. To achieve this, we felt that it was necessary to make some suggestions for both students and Teachers of French. The wrongful sentences were opposed to those deemed correct before determining the causes of these various faults. The objective of this article is to contribute to the improvement of the practice of French by students. To achieve this, we felt that it was necessary to make some suggestions for both students and Teachers of French.